Empowering patients to link to care and treatment: qualitative findings about the role of a home-based HIV counselling, testing and linkage intervention in South Africa - Knight, Lucia C. (AIDS Care, 2015)
To explore the barriers and facilitators of linkage to and retention in care amongst persons who tested positive for HIV, qualitative research was conducted in a home-based HIV counselling and testing (HBCT) project with interventions to facilitate linkages to HIV care in rural KwaZulu-Natal, South Africa. The intervention tested 1,272 adults for HIV in Vulindlela of whom 32% were HIV-positive, received point-of-care (POC) CD4 testing and referral to local HIV clinics. Those testing positive also received follow-up visits from a counsellor to evaluate linkages to care. The study employed a qualitative methodology collecting data through in-depth semi-structured interviews. Respondents included 25 HIV-positive persons who had tested as part of HBCT project, 4 intervention research counsellors who delivered the HBCT intervention and 9 government clinic staff who received referrals for care. The results show that HBCT helped to facilitate linkage to care through providing education and support to help overcome fears of stigma and discrimination. The results show the perceived value of receiving a POC CD4 result during post-test counselling, both for those newly diagnosed and those previously diagnosed as HIV positive. The results also demonstrate that in-depth counselling creates an ‘educated consumer’ facilitating engagement with clinical services. The study provides qualitative insights into the acceptability of confidential HBCT with same day POC CD4 testing and ART counselling as factors that influenced HIV-positive persons’ decisions to link to care. This model warrants further evaluation in non-research settings to determine impact and cost-effectiveness relative to other HIV testing and referral strategies.